KOLOMYIA PRESS IN THE PERIOD OF THE UKRAINIAN STATEHOOD AS A SOURCE FOR STUDYING THE LITERARY LIFE IN PRYKARPATTIA - Vasylchuk, M. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The author of the article examines periodical publications of Kolomyia of the middle of the 1980s − the first half of the 1990s from the point of view of employing their informational potential as a resource base to study the newest literary processes in Prykarpattia. The researcher touches upon a question of significance of the local printed mass media in revealing and engaging beginning authors in literary work. He introduces the notion about a cultural-historical epoch in journalism.